2000
DOI: 10.1177/07417130022086928
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Inhibitors to Informal Learning in the Workplace: A Case Study of Public School Teachers

Abstract: The purpose of this study was to examine environmental inhibitors to informal learning in the workplace. Twenty-two experienced teachers were interviewed and numerous site visits were made to each school where these teachers worked to develop a greater understanding of the ways in which aspects of their work environment inhibited them from engaging in informal learning. Four environmental inhibitors emerged from an analysis of the data: lack of time for learning, lack of proximity to learning resources, lack o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
125
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 10 publications
6
125
0
5
Order By: Relevance
“…Situational inhibitor refers to situational factors within a working environment that can reduce professionals' ability to gain access to, and pursue informal learning opportunities (Cross, 1981;Lohman, 2000). Therefore, situational inhibitors in this paper refer to situational factors within a public accounting firm environment that can inhibit accountants from informal learning activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Situational inhibitor refers to situational factors within a working environment that can reduce professionals' ability to gain access to, and pursue informal learning opportunities (Cross, 1981;Lohman, 2000). Therefore, situational inhibitors in this paper refer to situational factors within a public accounting firm environment that can inhibit accountants from informal learning activities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also in terms of teacher learning, the social side of learning is emphasised based on the idea that cognition is situated in nature (e.g. Kwakman, 2003;Lohman, 2000Lohman, , 2006Meredith, Van den Noortgate, Struyve, Gielen, & Kyndt, 2017;Van Waes, Van den Bossche, Moolenaar, De Maeyer & Van Petegem, 2015). A shift from a focus on the individual towards a more social approach contributed to the popularity of social network research methods to investigate relationships of teachers (Baker-Doyle, 2015).…”
Section: The Social Side Of Learning Across Generationsmentioning
confidence: 99%
“…In a similar study, most of the teachers reported the lack of proximity to learning resources (Lohman, 2000). In this study, although teachers in some elite schools have an annual budget to add new resources to their school library, most mainstream schools do not have that luxury.…”
Section: Individual Inquirymentioning
confidence: 50%
“…For example, Lohman (2000) has listed four such inhibitors and these are: lack of time for learning; lack of proximity to learning resources; lack of meaningful rewards for learning; and limited decision-making power.…”
mentioning
confidence: 99%
See 1 more Smart Citation